2016
DOI: 10.3390/en9100828
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Data Hierarchical Fusion Method for Gas Turbine Engine Performance Fault Diagnosis

Abstract: Gas path fault diagnosis involves the effective utilization of condition-based sensor signals along engine gas path to accurately identify engine performance failure. The rapid development of information processing technology has led to the use of multiple-source information fusion for fault diagnostics. Numerous efforts have been paid to develop data-based fusion methods, such as neural networks fusion, while little research has focused on fusion architecture or the fusion of different method kinds. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The algorithm works well in situations with high data conflict [18]. Furthermore, Lu et al [19] have confirmed the effectiveness and usefulness of fuzzy logic combined with an extension of DS theory in data fusion. In land cover classification, DS theory and fuzzy-contextual information [20] have been used in the classification of multispectral satellite images.…”
Section: Introductionmentioning
confidence: 84%
“…The algorithm works well in situations with high data conflict [18]. Furthermore, Lu et al [19] have confirmed the effectiveness and usefulness of fuzzy logic combined with an extension of DS theory in data fusion. In land cover classification, DS theory and fuzzy-contextual information [20] have been used in the classification of multispectral satellite images.…”
Section: Introductionmentioning
confidence: 84%
“…Gas turbines are widely used as the main power source in many areas, such as aircraft, ships, oil and gas applications, and power generation. Reducing maintenance costs and increasing the availability of gas turbines are two essential issues for equipment owners [1,2]. Prognostics and health management (PHM) can solve these problems and ensure that gas turbines run safely and economically [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The extreme learning machine (ELM) [11] is a recent ML method and introduced for wind speed forecasting because of its simple structure, fast learning rate, and strong generalization ability, and it effectively eliminates the risk of falling into a local optimum [12][13][14]. The kernel-based extreme learning machine (KELM) method [15] is an improved ELM method based on a kernel function that provides better approximations and generalizes more steadily than the original ELM method [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%